Analisis Kinerja Keuangan Perusahaan: Studi Kasus pada Perusahaan Sub Sektor Perusahaan Rokok yang tercatat di BEI Periode 2020-2022 - Sekar Setyoningrum; Caecilia Austin Flacia T; Joko Isworo; Yus Dakaria; Faula Fardhotin R; Yanuar Ramadhan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Evaluation of an organization's monetary exhibition is significant as a method or pointer to further develop the organization's functional exercises, so it is trusted that the organization can encounter better monetary development and can likewise rival different organizations. The point of this exploration is to investigate and survey the monetary exhibition of Cigarette Sub-Area Organizations recorded on the BEI for the 2020-2022 period in view of liquidity proportions, dissolvability proportions, action proportions and productivity proportions, as well as examination of monetary execution patterns. The scientific techniques utilized in this exploration are Monetary Proportion Examination and Patterns Examination. Based on overall financial ratios, the research shows that PT. H.M. Sampoerna, Tbk., has the best monetary presentation when contrasted with other Cigarette Organization Sub-Area Organizations. Even though a company is in a liquid state, it is likely that companies in the cigarette subsector that have a level of liquidity that is higher than the average for similar industries will be able to maintain and increase their ability to pay short-term debt. However, it would be even better if the company increased its liquidity. In the meantime, for cigarette sub-area organizations that have liquidity levels beneath the normal for comparative enterprises, they can expand their capacity to pay their momentary obligation.